Civil Society, Public Sphere and the Regulation of Ministry of Education and Culture Number 30 of 2021 - Krisnaldo Triguswinri; Hartuti Purnaweni; Budi Puspo Priyadi (Syntax Corporation, 2023)
The origins of civil society’s involvement in policies aimed at preventing and handling the sexual harassment cases which occur in college are caused by many sexual harassments, so civil society perceives that regulation which concerns on sexual harassment is needed as one of the steps to improve procedures for respecting the women’s dignity as stipulated in the Regulation of Ministry of Education and Culture Number 30 of 2021. This study uses qualitative approach, with the data collection method in the form of interviews with stakeholders representing country and civil society